The Impact of Water Resource Utilization on Afghanistan's International Relations: Challenges and Opportunities for Transboundary Water Management - Noorani Wafa; Fayaz Gul Mazloum Yar (Publikasi Indonesia, 2024)
Water resources are among the most vital natural elements and play a significant role in international relations, particularly for countries that rely heavily on these resources. This study examines the impact of water resource management on Afghanistan's international relations, particularly with neighboring countries such as Iran, Pakistan, and Tajikistan. As a landlocked nation, Afghanistan relies heavily on its water resources, which are crucial to its political, economic, and social stability. Mismanagement and unsustainable use of these shared resources can lead to international tensions, social unrest, and environmental degradation. Using both qualitative and quantitative methods, the research analyzes the opportunities and challenges associated with water resource management. It emphasizes the need for international cooperation, legal frameworks, and modern technologies. The findings suggest that effective water resource management can foster regional cooperation and improve Afghanistan's socio-economic conditions, while inadequate policies may heighten tensions. The study offers strategic recommendations to address these challenges and promote sustainable development.